Raltegravir pharmacokinetics before and during treatment with ombitasvir, paritaprevir/ritonavir plus dasabuvir in adults with human immunodeficiency virus‐1 and hepatitis C virus coinfection: AIDS Clinical Trials Group sub‐study A5334s. Issue 1 (12th December 2019) - Venuto, Charles S.; Cramer, Yoninah S.; Rosenkranz, Susan L.; Sulkowski, Mark; Wyles, David L.; Cohen, Daniel E.; Schmidt, Jeffrey; Alston‐Smith, Beverly L.; Morse, Gene D.
Abstract : Aims: AIDS Clinical Trials Group study A5334s evaluated the pharmacokinetics of raltegravir before and during combined administration of ombitasvir, paritaprevir/ritonavir, plus dasabuvir (OBV/PTV/r + DSV) and weight‐based ribavirin in human immunodeficiency virus (HIV) and hepatitis C virus (HCV) coinfected adults. The pharmacokinetics of OBV/PTV/r + DSV during raltegravir coadministration were also characterized. Methods: Adults living with HIV/HCV coinfection receiving steady‐state raltegravir (400 mg twice daily) with 2 nucleos(t)ide analogues were enrolled. Pharmacokinetics of raltegravir were assessed prior to HCV therapy, and 4 weeks later following initiation of OBV/PTV/r (25/150/100 mg) once daily + DSV (250 mg) twice daily. Geometric mean ratios (GMRs) and 90% confidence intervals (CIs) were used to compare the following: raltegravir pharmacokinetics with HCV therapy (week 4) vs before HCV therapy (week 0); OBV/PTV/r and DSV pharmacokinetics vs historical healthy controls; raltegravir pharmacokinetics at week 0 vs historical control adults living with HIV. Results: Eight of 11 participants had decreased raltegravir exposures after initiation of HCV therapy. The GMRs (90% CI) for maximum concentration and area under the concentration–time curve of raltegravir with vs without HCV therapy were 0.68 (0.38–1.19) and 0.82 (0.58–1.17), respectively. Comparing OBV/PTV/r pharmacokinetics in healthy controls, A5334s study participants demonstrated generally lower maximum concentration and area under the concentration–time curve values by 41–82% and 4–73%, respectively. Raltegravir exposures tended to be higher in A5334s study participants compared to adults living with HIV. Conclusions: The majority of participants' plasma raltegravir exposures were lower after initiation of HCV therapy in coinfected adults; however, confidence intervals were wide.